The application of technology devices in commissary catering kitchen establishments - Hamid, Munirah; Mohd Zahari, Mohd Salehuddin; Abd Ghani, Fatimah; Jusoff, Kamaruzaman; Ramli, Noorazlin; Md. Zaini, Zetty Madina; Rahmat, Norazlina; Ngali, Norzaidah; Samsudin, Azlina (IDOSI Publications, 2011)
Technology is undeniably very important in food service industry. This study empirically investigated the application of technology in Malaysia commissary catering establishments and how it implicated the productivity. Using semi-structured interviews with managers and questionnaire survey with employees of four commissary catering establishments, some meaningful insights on the topic of interest were obtained. The application of technology had brought vast benefits to commissary establishments. Technology used not only increased the speed, volume, quality and cleanliness but also helped in smooth running of the food production and most importantly boosted the productivity of the commissary catering establishment. These findings produced significant indicators not only to those who are already in commissary catering but also to those individuals or companies who intent to venture into food service businesses.